HEALTH PROMOTION IN LOW AND MIDDLE INCOME COUNTRIES: âYOUTH CHAMPIONSâ AS AGENTS OF CHANGE - Mukisa, Ronald; Macnab, Andrew J; Stothers, Lynn (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Health promotion includes a wide range of social and environmental interventions that enable people to increase control over their own health. The aim is to achieve health literacy, where people have the knowledge they need to make healthy choices and the skills and daily practices necessary to improve their health, and can access information that helps to reduce the risk of illness or injury. Health promotion programs traditionally use adult experts or teachers to deliver the information and practices promoted, but in school-based programs WHO advocates the involvement of youth to make program content and delivery relevant and interesting to school children. Aims: To summarize how youth leaders (âchampionsâ) can contribute to school and community based programs through their involvement in the design of school-based health promotion and by engaging and motivating the target population. Methods: Summary of the HPS literature and experience of youth involvement in our school programs in Africa Results: Schools are settings where important health knowledge and behaviours can be promoted. Teachers have a central role in creating an environment that fosters health learning, but the efficacy of health promotion is improved when youth are included in program design and delivery. Youth champions have a special ability to connect with the target audience in schools and by using the pupils âlanguageâ and idioms make the knowledge and practices being shared relevant and accessible. Trained youth can champion individual messages or take on a variety of roles in health promotion initiatives. Youth champions have contributed to the success of programs that have promoted hand washing, oral health, improved nutrition, malaria prevention, sexual health and HIV/Aids prevention Youth involved as champions have an important opportunity to learn as well as to contribute; potentially, many educators, health care providers and leaders of tomorrow will emerge from among them.. Conclusion: Youth who act as champions and peer to peer counsellors have a unique contribution to make in school-based health promotion. As measured by long term retention of knowledge and sustained changes in behavior, school-based health promotion is improved when youth are included as âmessengersâ and pupils help select the âmessagesâ promoted.Â